Electrolyte additive, electrolyte and lithium ion secondary battery comprising electrolyte additive

By using electrolyte additives with specific structures in lithium-ion secondary batteries, a protective film can be formed at the same time on the positive electrode and the negative electrode of the battery, solving the problem of insufficient protection of battery electrodes in the prior art, improving the cycling performance of the battery and reducing impedance.

CN119864504APending Publication Date: 2025-04-22MURATA MFG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311369963.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The method of preparing lithium-ion secondary batteries in the prior art cannot effectively protect the electrodes, resulting in the battery showing poor cycle retention and post-cycle impedance.

Method used

An electrolyte additive is provided, which comprises a compound of a specific structure, such as a substance composed of R1, R2, R3, R4, wherein R2 to R4 contain at least one F atom, which can simultaneously undergo redox reactions on the positive electrode and the negative electrode of the battery to form an SEI film and a CEI film to protect the electrode.

Benefits of technology

By using the electrolyte additive, the cycling performance of the battery is improved, the impedance after cycling is reduced, and the gas production effect of the battery is suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864504A_ABST
    Figure CN119864504A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte additive, an electrolyte and a lithium ion secondary battery containing the electrolyte additive. The electrolyte additive includes a substance represented by the following formula (1), in which R1 is a substituted or unsubstituted six-membered heterocyclic compound, and R2 to R4 are each independently selected from the group consisting of H, F, and unsubstituted or F-substituted C1-6 alkanes, with the proviso that at least one F atom is included in R2 to R4. According to the electrolyte additive, the electrolyte and the lithium ion secondary battery comprising the electrolyte additive, the electrolyte and the lithium ion secondary battery, an electrode is better protected, the cycle performance of the battery is improved, lower post-cycle impedance is realized, and the gas production effect of the battery is inhibited. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion secondary batteries, and in particular to an electrolyte additive, an electrolyte and a lithium ion secondary battery containing the same. Background Art

[0002] In recent years, with the continuous updating of electronic technology, people's demand for battery devices used to support the energy supply of electronic devices has also been increasing. Nowadays, batteries that can store more electricity and output high power are needed. Traditional lead-acid batteries and nickel-metal hydride batteries can no longer meet the needs of new electronic products such as mobile devices such as smartphones and fixed equipment such as power storage systems. Therefore, lithium batteries have attracted widespread attention. In the process of developing lithium batteries, their capacity and performance have been effectively improved.

[0003] In the process of developing electrolytes for lithium-ion secondary batteries, it was found that adding electrolyte additives would help protect the battery electrodes from being corroded by electrolyte solvents. In the process of forming the battery (the first charge and discharge cycle), the electrolyte additives will be superior to the electrolyte solvents in decomposition and form a film on the surface of the positive or negative electrode, thereby protecting the electrode. The mechanism of action of additives and solvents in batteries is different. When the additive forms a film at the positive electrode, it is easier to lose electrons at the positive electrode and be oxidized to form a CEI film (positive electrode electrolyte interface film). When the additive forms a film at the negative electrode, it is easier to get electrons at the negative electrode and be reduced to form a SEI film (solid electrolyte interface film). The solvent needs to have a certain electrochemical stability and not be oxidized or reduced during the battery charge and discharge process, resulting in failure. Different types of electrolyte additives are usually used in the prior art, so that different types of electrolyte additives are simultaneously formed on the positive and negative electrode surfaces in the first cycle of the lithium-ion secondary battery. However, the method for preparing lithium ion secondary batteries used in the prior art cannot effectively protect the electrodes, so that the battery exhibits poor cycle retention and post-cycle impedance.

[0004] Therefore, in order to solve the above-mentioned problems, it is still necessary to develop electrolyte additives that can effectively form SEI films and SEI films and ensure the electrical performance of lithium-ion secondary batteries. Summary of the invention

[0005] The main purpose of the present invention is to provide an electrolyte additive, an electrolyte and a lithium ion secondary battery containing the same, so as to solve the problem that the method for preparing lithium ion secondary batteries in the prior art cannot effectively protect the electrodes, thereby causing the battery to exhibit poor cycle retention and post-cycle impedance.

[0006] In order to achieve the above object, according to one aspect of the present invention, there is provided an electrolyte additive, comprising a substance represented by the following formula (1):

[0007]

[0008] wherein R1 is a substituted or unsubstituted six-membered heterocyclic compound, and R2 to R4 are each independently selected from H, F, unsubstituted or F-substituted C 1-6 The group consisting of alkanes, provided that R2 to R4 contain at least one F atom.

[0009] Furthermore, in the above electrolyte additive, in the substance represented by formula (1), wherein R1 is C 1-3 An alkane or alkene substituted or unsubstituted six-membered heterocyclic compound, wherein the number of heteroatoms is 1-3 and the heteroatom is N.

[0010] Furthermore, in the above electrolyte additive, in the substance represented by formula (1), R1 is pyrimidine, pyridine, pyridazine, pyrazine, 1,2,3-triazine, 1,2,4-triazine or 1,3,5-triazine.

[0011] Furthermore, in the above electrolyte additive, R2 to R4 are each independently selected from H, F, unsubstituted or F-substituted C 1-3 The group consisting of alkanes; preferably, R2 to R4 are each independently selected from the group consisting of H, F, CH3, CH2F, CHF2, CF3 and C2H5.

[0012] Furthermore, in the above electrolyte additive, the substance represented by formula (1) is selected from the following substances:

[0013]

[0014] According to another aspect of the present invention, an electrolyte is provided, comprising an organic solvent, a lithium salt and the electrolyte additive described above.

[0015] Further, in the above electrolyte, based on 100 parts by weight of the total weight of the organic solvent and the lithium salt, the amount of the electrolyte additive is in the range of 0.3 parts by weight to 2.0 parts by weight; preferably, the amount of the electrolyte additive is in the range of 0.5 parts by weight to 1.5 parts by weight.

[0016] Furthermore, in the above electrolyte, the electrolyte further comprises a film-forming additive.

[0017] Further, in the above-mentioned electrolyte, based on 100 parts by weight of the total weight of the organic solvent and the lithium salt, the amount of the electrolyte additive is in the range of 0.1 parts by weight to 1.0 parts by weight, and the amount of the film-forming additive is in the range of 2.0 parts by weight to 12.0 parts by weight; preferably, the amount of the electrolyte additive is in the range of 0.3 parts by weight to 0.5 parts by weight, and the amount of the film-forming additive is in the range of 2.25 parts by weight to 11.50 parts by weight.

[0018] Furthermore, in the above electrolyte, the film-forming additive is selected from fluoroethylene carbonate, vinylene carbonate, halogenated cyclic carbonate, sulfonate, acid anhydride, polynitrile compound, diisocyanate compound, phosphate, borate or any combination thereof.

[0019] Furthermore, in the above-mentioned electrolyte, the lithium salt is selected from LiCl, LiBr, LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2F)2, LiN(SO2CF3)2, LiC(SO2CF3)3, LiAlCl4, LiSiF6, or any group thereof.

[0020] Furthermore, in the above electrolyte, the organic solvent is selected from ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate or any combination thereof.

[0021] According to another aspect of the present invention, there is provided a lithium-ion secondary battery, comprising: a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte described above.

[0022] The electrolyte additive, electrolyte and lithium ion secondary battery containing the same of the present invention achieve better protection of electrodes, improve battery cycle performance, achieve lower post-cycle impedance and inhibit battery gas generation. DETAILED DESCRIPTION

[0023] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments. The following embodiments are merely exemplary and do not constitute a limitation on the scope of protection of the present invention.

[0024] As described in the background art, in the prior art, the electrolyte additive added to the lithium ion secondary battery cannot effectively protect the positive electrode and the negative electrode of the battery, and adversely deteriorates the electrical performance of the lithium ion secondary battery. In view of the problems in the prior art, a typical embodiment of the present invention provides an electrolyte additive, which comprises a substance represented by the following formula (1):

[0025]

[0026] wherein R1 is a substituted or unsubstituted six-membered heterocyclic compound, and R2 to R4 are each independently selected from H, F, unsubstituted or F-substituted C 1-6 The group consisting of alkanes, provided that R2 to R4 contain at least one F atom.

[0027] In the prior art, it is necessary to use a variety of different types of electrolyte additives to form CEI films and SEI films on the positive and negative electrodes of the battery. Different from the electrolyte additives in the prior art, the electrolyte additives of the present application can simultaneously undergo redox reactions at the positive and negative electrodes of the battery, and deposit the products on the positive and negative electrodes, thereby simultaneously forming SEI films and CEI films on their surfaces.

[0028] The electrolyte additive of the present invention is shown in the above formula (1), wherein the R1 group on the left is a substituted or unsubstituted six-membered heterocyclic compound, which achieves the decomposition reaction activity of the R2 group on the right during the electrochemical reaction through the conjugation effect of the electron transfer of the six-membered heterocyclic compound. And after decomposition, the decomposition product obtained forms a film on the electrode surface, thereby playing a role in protecting the electrode. After the compound of formula (1) decomposes, the S-containing decomposition product has a good lithium ion conduction effect, thereby improving the impedance of the battery. After the compound of formula (1) decomposes, its product can interact with the nickel ions of the positive electrode, stabilize the positive electrode material from being corroded by the electrolyte, and inhibit the gas production of the battery.

[0029] In addition, the compound of formula (1) of the present invention undergoes redox reactions simultaneously at the positive and negative electrodes, thereby forming a SEI film and a CEI film with low impedance components at the positive and negative electrodes and reducing the battery impedance. On the other hand, it can inhibit the dissolution of transition metals, thereby improving the cycle performance of the battery.

[0030] In some embodiments, in the compound represented by the above formula (1) of the present invention, R1 is a substituted or unsubstituted six-membered heterocyclic compound, the number of heteroatoms is 1-3 and the heteroatom is N. Since the compound represented by formula (1) contains N atoms or S atoms, after the decomposition product is deposited on the positive electrode and the negative electrode, the N atoms and S atoms contained therein can interact with the free lithium ions in the electrolyte, thereby improving the insertion and deinsertion of lithium ions relative to the electrode and improving the transmission efficiency of lithium ions.

[0031] In some preferred embodiments of the present invention, in the compound of the above formula (1) of the present invention, R1 is pyrimidine, pyridine, pyridazine, pyrazine, 1,2,3-triazine, 1,2,4-triazine or 1,3,5-triazine. More preferably, R1 is pyrimidine, pyridine or pyridazine.

[0032] In some embodiments, in the compound represented by the above formula (1) of the present invention, R2 to R4 are each independently selected from H, F, unsubstituted or F-substituted C 1-3 The group consisting of alkanes; preferably, R2 to R4 are each independently selected from the group consisting of H, F, CH3, CH2F, CHF2, CF3 and C2H5.

[0033] In a preferred embodiment of the present invention, the chemical formula of formula (1) can be selected from the group consisting of:

[0034]

[0035]

[0036]

[0037] In a further preferred embodiment, the chemical formula of formula (1) can be selected from the group consisting of:

[0038]

[0039]

[0040] In a more preferred embodiment, the chemical formula of formula (1) can be selected from the group consisting of:

[0041]

[0042] In another typical embodiment of the present invention, an electrolyte is provided, comprising an organic solvent, a lithium salt, and the electrolyte additive described above. Due to the inclusion of the electrolyte additive of the present invention, the electrolyte of the present invention can more effectively form a CEI film on the positive electrode surface and a SEI film on the negative electrode surface during the first cycle of the battery, thereby inhibiting the decomposition of the solvent. In addition, after the electrolyte additive described above decomposes, the decomposition product containing S has a good lithium ion conductivity, thereby improving the impedance of the battery, and its decomposition product can interact with the nickel ions of the positive electrode, stabilize the positive electrode material from being corroded by the electrolyte, and inhibit the gas production of the battery.

[0043] In some embodiments of the present invention, in the electrolyte of the present invention, the amount of the electrolyte additive is in the range of 0.3 to 2.0 parts by weight based on 100 parts by weight of the total weight of the organic solvent and the lithium salt. In a preferred embodiment, in the electrolyte of the present invention, the amount of the electrolyte additive is in the range of 0.5 to 1.5 parts by weight based on 100 parts by weight of the total weight of the organic solvent and the lithium salt. Within the above-mentioned weight range, the electrolyte additive can be quickly decomposed in the first cycle of the battery and attached to the positive and negative electrodes to form SEI films and CEI films. In the case of using only the electrolyte additive of the present invention, if the amount of the electrolyte additive is less than 0.3 parts by weight, the SEI film and CEI film formed will not be able to be completely attached to the positive and negative electrodes, and in the subsequent use process, the solvent will corrode the electrodes unfavorably and affect the electrical properties of the battery, such as increasing the battery impedance, reducing the cycle retention rate, etc. If the amount of the electrolyte additive is greater than 2.0 parts by weight, the added electrolyte additive will not be completely decomposed and remain in the electrolyte or directly adhere to the electrode without being decomposed, so that the impedance of the electrolyte or electrode surface increases, adversely reducing the electrical performance of the battery.

[0044] In different embodiments of the present invention, according to different combinations of lithium salts and organic solvents, the minimum amount of the electrolyte additive contained in the electrolyte, based on 100 parts by weight of the total weight of the organic solvent and the lithium salt, should be greater than 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight, 1.0 parts by weight, 1.1 parts by weight, 1.2 parts by weight, 1.3 parts by weight, 1.4 parts by weight, 1.5 parts by weight, 1.6 parts by weight, 1.7 parts by weight, 1.8 parts by weight or 1.9 parts by weight. Furthermore, according to different combinations of organic solvents and lithium salts, the maximum amount of the electrolyte additive contained in the electrolyte should be less than 2.0 parts by weight, 1.9 parts by weight, 1.8 parts by weight, 1.7 parts by weight, 1.6 parts by weight, 1.5 parts by weight, 1.4 parts by weight, 1.3 parts by weight, 1.2 parts by weight, 1.1 parts by weight, 1.0 parts by weight, 0.9 parts by weight, 0.8 parts by weight, 0.7 parts by weight, 0.7 parts by weight, 0.6 parts by weight, 0.5 parts by weight or 0.4 parts by weight based on 100 parts by weight of the total weight of the organic solvent and the lithium salt.

[0045] Specifically, based on 100 parts by weight of the total weight of the organic solvent, the lithium salt and the film-forming additive, the amount of the electrolyte additive in the electrolyte can be in the following ranges: 0.3 parts by weight to 2.0 parts by weight, 0.4 parts by weight to 1.9 parts by weight, 0.5 parts by weight to 1.8 parts by weight, 0.6 parts by weight to 1.7 parts by weight, 0.7 parts by weight to 1.8 parts by weight, 0.8 parts by weight to 1.7 parts by weight, 0.9 parts by weight to 1.8 parts by weight, 1.0 parts by weight to 1.7 parts by weight, 1.1 parts by weight to 1.6 parts by weight, 1.2 parts by weight to 1 .5 parts by weight, 1.3 parts by weight to 1.4 parts by weight, 0.3 parts by weight to 1.9 parts by weight, 0.3 parts by weight to 1.8 parts by weight, 0.3 parts by weight to 1.7 parts by weight, 0.3 parts by weight to 1.6 parts by weight, 0.3 parts by weight to 1.5 parts by weight, 0.4 parts by weight to 2.0 parts by weight, 0.5 parts by weight to 2.0 parts by weight, 0.5 parts by weight to 1.9 parts by weight, 0.5 parts by weight to 1.8 parts by weight, 0.5 parts by weight to 1.7 parts by weight, 0.5 parts by weight to 1.6 parts by weight or 0.5 parts by weight to 1.5 parts by weight.

[0046] In a further embodiment of the present invention, the electrolyte of the present invention may further include a film-forming additive. When the film-forming additive is used together with the electrolyte additive described above, the inventors of the present invention surprisingly found that the cycle retention rate of the prepared lithium ion secondary battery is further improved. In addition, the electrolyte additive of the present invention can have a good lithium ion conduction effect after forming an electrode film. When the film-forming additive and the electrolyte additive are added at the same time, the impedance of the formed battery can be maintained at a low level.

[0047] In an embodiment in which the electrolyte contains both a film-forming additive and an electrolyte additive, the amount of the electrolyte additive is in the range of 0.1 to 1.0 parts by weight based on 100 parts by weight of the total weight of the organic solvent and the lithium salt, and the amount of the film-forming additive is in the range of 2.0 to 12.0 parts by weight. In a further preferred embodiment, the amount of the electrolyte additive is in the range of 0.3 to 0.5 parts by weight based on 100 parts by weight of the total weight of the organic solvent and the lithium salt, and the amount of the film-forming additive is in the range of 2.25 to 11.50 parts by weight. Within the above-mentioned weight range, the film-forming additive and the electrolyte additive can simultaneously form a protective film on the surface of the positive electrode and / or the negative electrode during the first cycle of the lithium-ion secondary battery, protecting the electrode from being corroded by the solvent and providing good lithium ion transmission capacity.

[0048] Specifically, in different embodiments of the present invention, according to different combinations of lithium salts, organic solvents, electrolyte additives and film-forming additives, based on 100 parts by weight of the total weight of the organic solvent, the lithium salt and the film-forming additive, the amount of the electrolyte additive in the electrolyte can be in the following range: 0.1 parts by weight to 1.0 parts by weight, 0.2 parts by weight to 0.9 parts by weight, 0.3 parts by weight to 0.8 parts by weight, 0.4 parts by weight to 0.7 parts by weight, 0.5 parts by weight to 0.6 parts by weight, 0.1 parts by weight to 0.9 parts by weight, 0.1 parts by weight to 0.8 parts by weight, 0.1 parts by weight to 0.7 parts by weight, 0.1 parts by weight to 0.6 parts by weight, 0.1 parts by weight to 0.5 parts by weight, 0.2 parts by weight to 1.0 parts by weight, 0.3 parts by weight to 1.0 parts by weight, 0.3 parts by weight to 0.9 parts by weight, 0.3 parts by weight to 0.8 parts by weight, 0.3 parts by weight to 0.7 parts by weight. parts by weight, 0.3 parts by weight to 0.6 parts by weight or 0.3 parts by weight to 0.5 parts by weight; and the amount of the film-forming additive in the electrolyte may be in the following ranges: 2.0 parts by weight to 12.0 parts by weight, 2.0 parts by weight to 11.9 parts by weight, 2.0 parts by weight to 11.8 parts by weight, 2.0 parts by weight to 11.7 parts by weight, 2.0 parts by weight to 11.6 parts by weight, 2.0 parts by weight to 11.5 parts by weight, 2.1 parts by weight to From 2.25 parts by weight to 11.6 parts by weight, or from 2.25 parts by weight to 11.5 parts by weight.

[0049] In the present invention, the film-forming additive that can be used is selected from fluoroethylene carbonate (FEC), vinylene carbonate, halogenated cyclic carbonate, sulfonate, anhydride, polynitrile compound, diisocyanate compound, phosphate, borate or any combination thereof. These film-forming additives can be used alone. In some embodiments of the present invention, the preferred film-forming additive is fluoroethylene carbonate.

[0050] The present invention has no particular restrictions on the lithium salt components contained in the electrolyte, and those known in the prior art that can be used for lithium battery electrolytes can be adopted. Examples of lithium salts include, but are not limited to: LiCl, LiBr, LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2F)2, LiN(SO2CF3)2, LiC(SO2CF3)3, LiAlCl4, LiSiF6, or any combination thereof.

[0051] In the present invention, the organic solvent used in the electrolyte can be any non-aqueous solvent used for non-aqueous electrolyte solutions to date. Examples include, but are not limited to: linear or cyclic carbonates, such as ethylene carbonate, propylene carbonate, butylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, fluoroethylene carbonate; ethers, such as 1,2-dimethoxyethane, 1,2-diethoxyethane, γ-butyrolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, diethyl ether; sulfones, such as cyclopentane sulfone, methylcyclopentane sulfone; nitriles, such as acetonitrile, propionitrile, acrylonitrile; esters, such as acetate, propionate, butyrate, etc. These non-aqueous solvents can be used alone or in combination. In some embodiments of the present invention, preferred electrolyte comprises ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate or any combination thereof. In a preferred embodiment, at least one carbonate is used as the organic solvent of electrolyte of the present invention. In other preferred embodiments, the above-mentioned non-aqueous solvent can be used in any combination to form an electrolyte solution that meets specific requirements.

[0052] In another typical embodiment of the present invention, a lithium ion secondary battery is provided, which includes: a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte described above. Since the lithium ion secondary battery of the present invention uses the electrolyte described above, it has excellent cycle performance and reduced impedance.

[0053] The positive electrode sheet of the present invention includes a positive electrode current collector and a positive electrode active material layer containing a positive electrode active material. The positive electrode active material layer is formed on both surfaces of the positive electrode current collector. A metal foil such as aluminum foil, nickel foil, and stainless steel foil can be used as the positive electrode current collector.

[0054] The positive electrode active material layer contains one or two or more kinds of positive electrode materials that can absorb and release lithium ions as the positive electrode active material, and may contain additional materials such as a positive electrode binder and / or a positive electrode conductive agent when necessary.

[0055] Preferably, the positive electrode material is a lithium-containing compound. Examples of such lithium-containing compounds include lithium-transition metal composite oxides, lithium-transition metal phosphate compounds, and the like. The lithium-transition metal composite oxide is an oxide containing Li and one or two or more transition metal elements as constituent elements, and the lithium-transition metal phosphate compound is a phosphate compound containing Li and one or two or more transition metal elements as constituent elements. Among them, the transition metal element is advantageously any one or two or more of Co, Ni, Mn, Fe, etc.

[0056] Examples of the lithium-transition metal composite oxide include, for example, LiCoO2, LiNiO2, etc. Examples of the lithium-transition metal phosphate compound include, for example, LiFePO4, LiFe 1-u Mn u PO4 (0 < u < 1), etc.

[0057] In some embodiments of the present application, the positive electrode material may be a ternary positive electrode material, such as lithium nickel cobalt aluminate (NCA) or lithium nickel cobalt manganate (NCM). Specific examples may be NCA, LixNiyCozAl1-y-zO2 (1 ≤ x ≤ 1.2, 0.5 ≤ y ≤ 1, and 0 ≤ z ≤ 0.5); and NCM, LiNixCoyMnzO2 (x + y + z = 1, 0 < x < 1, 0 < y < 1, 0 < z < 1). Specific examples of the positive electrode material may include, but are not limited to, the following materials: LiNiO2, LiCoO2, LiCo 0.98 Al 0.01 Mg 0.01 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.2 Mn 0.52 Co 0.175 Ni 0.1O2 and Li 1.15 (Mn 0.65 Ni 0.22 Co 0.13 )O2, LiFePO4, LiMnPO4, LiFe 0.5 Mn 0.5 PO4 and LiFe 0.3 Mn 0.7 PO4.

[0058] In addition, the positive electrode material may be, for example, any one or two or more of an oxide, a disulfide, a chalcogenide, a conductive polymer, etc. Examples of oxides include, for example, titanium oxide, vanadium oxide, manganese dioxide, etc. Examples of disulfides include, for example, titanium disulfide, molybdenum sulfide, etc. Examples of chalcogenides include, for example, niobium selenide, etc. Examples of conductive polymers include, for example, sulfur, polyaniline, polythiophene, etc. However, the positive electrode material may be a material different from those above.

[0059] Examples of positive electrode conductors include carbon materials such as graphite, carbon black, acetylene black and Ketjenblack. These can be used alone, or two or more of them can be mixed and used. It should be noted that the positive electrode conductor can be a metal material, a conductive polymer or the like, as long as it has conductivity.

[0060] Examples of positive electrode binders include, for example, synthetic rubber and polymer materials, where the synthetic rubber may be, for example, styrene-butadiene rubber, fluororubber and ethylene-propylene-diene, and the polymer material may be, for example, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, lithium polyacrylate, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM and polyimide. These may be used alone, or two or more thereof may be mixed and used.

[0061] The negative electrode sheet of the present invention includes a negative electrode collector and a negative electrode active material layer containing a negative electrode active material. The negative electrode active material layer is formed on both surfaces of the negative electrode collector. Metal foils such as copper foil, nickel foil and stainless steel foil can be used as the negative electrode collector.

[0062] The negative electrode active material layer contains a material capable of absorbing and releasing lithium ions as a negative electrode active material, and may contain other materials such as a negative electrode binder and / or a negative electrode conductor if necessary. The details of the negative electrode binder and the negative electrode conductor are, for example, the same as those of the positive electrode binder and the positive electrode conductor.

[0063] The active material of the negative electrode is selected from any one or more combinations of lithium metal, lithium alloy, carbon material, silicon or tin and oxides thereof.

[0064] Since carbon materials have a low potential when absorbing lithium ions, high energy density can be obtained and battery capacity can be increased. In addition, carbon materials also function as conductive agents. Such carbon materials are, for example, natural graphite, artificial graphite, materials obtained by coating them with amorphous carbon, or the like. It should be noted that the shape of the carbon material is fibrous, spherical, granular, flaky or the like. Silicon-based materials include nano-silicon, silicon alloys, SiO w The silicon-carbon composite material formed by compounding with graphite, preferably, the SiO w It is silicon monoxide, silicon oxide or other silicon-based materials.

[0065] In addition, the negative electrode material may be, for example, one or more of graphitizable carbon, difficult graphitizable carbon, metal oxides, polymer compounds, etc. Examples of metal oxides include, for example, iron oxide, ruthenium oxide, molybdenum oxide, etc. Examples of polymer compounds include, for example, polyacetylene, polyaniline, polypyrrole, etc. However, the negative electrode material may be another material different from those described above.

[0066] The separator of the present invention is used to separate the positive electrode sheet and the negative electrode sheet in the battery, and to allow ions to pass through while preventing the current short circuit caused by the contact between the two electrode sheets. The separator is, for example, a porous film formed of a synthetic resin, ceramic or the like, and can be a laminated film in which two or more porous films are laminated. Examples of synthetic resins include, for example, polytetrafluoroethylene, polypropylene, polyethylene, cellulose, etc.

[0067] In an embodiment of the present invention, when charging, for example, lithium ions are released from the positive electrode and absorbed in the cathode by the non-aqueous electrolyte impregnated in the separator. When discharging, for example, lithium ions are released from the negative electrode and absorbed in the positive electrode by the non-aqueous electrolyte impregnated in the separator.

[0068] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0069]

[0070] Example 1

[0071] Preparation of electrolyte

[0072] 20.8 g of ethylene carbonate, 56.7 g of dimethyl carbonate, 3.5 g of ethyl methyl carbonate, 0.4 g of lithium tetrafluoroborate and 18.6 g of lithium hexafluorophosphate were mixed to prepare a basic electrolyte. 0.5 g of electrolyte additive A-1 (as shown below) was added to the above electrolyte, and the electrolyte was obtained after stirring evenly.

[0073]

[0074] Preparation of the positive electrode

[0075] Mix 95.5 g of the positive electrode active material lithium nickel cobalt aluminate, 2.5 g of conductive carbon black, 1.9 g of polyvinylidene fluoride, and 0.1 g of dispersant to obtain a positive electrode mixture, and disperse the obtained mixture in N-methylpyrrolidone to obtain a positive electrode mixture slurry. Subsequently, coat the positive electrode mixture slurry onto the positive electrode current collector obtained from aluminum foil, dry the positive electrode current collector, and form the positive electrode plate using a stamping process.

[0076] Preparation of the negative electrode

[0077] Stir 95.85 g of a silicon monoxide (SiOx, 1 < x < 2) and graphite powder mixture (mass ratio 1:11), 1 g of SuperP, 3.15 g of binder CMC (sodium carboxymethyl cellulose) and SBR (styrene-butadiene rubber) (where the mass ratio of CMC to SBR is 1:1) and an appropriate amount of water to prepare a negative electrode slurry. Then uniformly coat the obtained negative electrode slurry onto copper foil to obtain the negative electrode current collector, dry the negative electrode current collector, and form the negative electrode plate using a stamping process.

[0078] Assembly of the battery

[0079] Assemble a CR2016 button cell in a dry laboratory. Use the positive electrode plate prepared in the above steps as the positive electrode, the negative electrode plate as the negative electrode, and the electrolyte prepared in the above steps as the electrolyte of the battery. Assemble the positive electrode, negative electrode, separator, and the battery case of the button cell. After the battery assembly is completed, let it stand for 24 h for aging to obtain a button battery.

[0080] Examples 2 - 11 and Comparative Examples 1 - 2

[0081] Prepare the batteries of Examples 2 - 11 and Comparative Examples 1 - 2 using the same method as in Example 1, and the differences are shown in Table 1 below

[0082] Table 1

[0083]

[0084]

[0085] Testing of battery performance

[0086] Measurement of charge-discharge capacity and determination of capacity retention rate

[0087] The first activation and cycle test were carried out on a Xinwei battery tester (model 5V-50mA). First, 0.1C charging and discharging were performed once at room temperature. Cycle test: 0.5C charging and 5C discharging cycle test was performed 100 times at 60°C.

[0088] Cycle retention rate after 100 cycles [%] = (discharge capacity at 100th cycle / discharge capacity at 1st cycle) × 100% Impedance measurement

[0089] The lithium-ion secondary battery was kept at room temperature, charged once at 0.5C, left standing at room temperature for 1 hour, and then the initial impedance value of the battery was tested by an electrochemical workstation, and the frequency range was (500MHz-50mHz). 100 charge-discharge cycles were performed at room temperature, and then a 0.5C charge test was performed once, and after standing at room temperature for 1 hour, the final impedance value of the battery was tested by an electrochemical workstation, and the frequency range was (500MHz-50mHz).

[0090] Impedance growth rate [%] = (final impedance value - initial impedance value) / initial impedance value × 100%

[0091] The experimental results are shown in Table 2 below.

[0092] Table 2

[0093]

[0094]

[0095] It can be seen from the data shown in Table 2 above that, compared with Comparative Example 1 in which the electrolyte additive of the present invention and any film-forming additive are not added, Examples 1-11 of the present invention all achieve significantly increased cycle retention rates, and the impedance after the cycle is also significantly reduced. For example, compared with Comparative Example 1, Example 7, which only adds the electrolyte additive of the present invention but does not add the film-forming additive, achieves a significantly increased cycle retention rate of an astonishing 11.71%, while the battery impedance growth rate after the cycle is reduced by 409%. In further Examples 8-11, the electrolyte additive of the present invention and the film-forming additive (FEC) are added to the electrolyte of the battery at the same time, and it can be seen from the experimental results that the cycle retention rate of the battery is further increased, and the battery impedance growth rate after the cycle is not only lower than that of Comparative Example 1 (without any additive), but even lower than the impedance growth rate of Comparative Example 2 in which only FEC is added.

[0096] Examples 12-25 and Comparative Examples 3-5

[0097] The batteries of Examples 12-25 and Comparative Examples 3-5 were prepared in the same manner as in Example 1. The differences are shown in Table 3 below.

[0098] Table 3

[0099]

[0100]

[0101]

[0102] Battery Gas Generation Test

[0103] The initial volume of the battery after final sealing was tested by the Archimedes drainage method; then a cycle test of 0.5C charging and 5C discharging was carried out at 60°C for 100 times, and the final volume of the battery was measured after completing 100 cycles.

[0104] Gas production [ml] = final volume - initial volume

[0105] The experimental results are shown in Table 4 below.

[0106] Table 4

[0107]

[0108]

[0109] It can be seen from the experimental results shown in Table 4 above that compared with Comparative Example 3 in which the electrolyte additive of the present invention and any film-forming additive are not added, Examples 12-25 of the present invention all show significantly reduced gas production. Compared with Comparative Example 4 in which only the film-forming additive FEC is used, although the FEC of Comparative Example 4 can suppress the gas production (0.62 ml), Example 14 of the present invention (including both the electrolyte additive and the film-forming additive FEC) shows a lower gas production (0.52 ml). In addition, when used together with a variety of different types of film-forming additives, such as Examples 15-17, the lithium ion secondary battery of the present invention also shows excellent gas production.

Claims

1. An electrolyte additive, characterized in that: Contains a substance represented by the following formula (1): in R1 is a substituted or unsubstituted six-membered heterocyclic compound, R2 to R4 are each independently selected from H, F, unsubstituted or F-substituted C 1-6 The group consisting of alkanes, Provided that R2 to R4 contain at least one F atom.

2. The electrolyte additive according to claim 1, characterized in that: In the substance represented by formula (1), wherein R1 is C 1-3 An alkane or alkene substituted or unsubstituted six-membered heterocyclic compound, wherein the number of heteroatoms is 1-3 and the heteroatom is N.

3. The electrolyte additive according to claim 2, characterized in that: In the substance represented by formula (1), R1 is pyrimidine, pyridine, pyridazine, pyrazine, 1,2,3-triazine, 1,2,4-triazine or 1,3,5-triazine.

4. The electrolyte additive according to claim 1, characterized in that: R2 to R4 are each independently selected from H, F, unsubstituted or F-substituted C 1-3 The group consisting of alkanes; preferably, R2 to R4 are each independently selected from the group consisting of H, F, CH3, CH2F, CHF2, CF3 and C2H5.

5. The electrolyte additive according to claim 1, characterized in that: The substance represented by formula (1) is selected from the following substances: 6 . An electrolyte comprising an organic solvent, a lithium salt and the electrolyte additive according to any one of claims 1 to 5.

7. The electrolyte according to claim 6, characterized in that Based on 100 parts by weight of the total weight of the organic solvent and the lithium salt, the amount of the electrolyte additive is in the range of 0.3 parts by weight to 2.0 parts by weight; preferably, the amount of the electrolyte additive is in the range of 0.5 parts by weight to 1.5 parts by weight.

8. The electrolyte according to claim 6, characterized in that The electrolyte further comprises a film-forming additive.

9. The electrolyte according to claim 8, characterized in that Based on 100 parts by weight of the total weight of the organic solvent and the lithium salt, the amount of the electrolyte additive is in the range of 0.1 parts by weight to 1.0 parts by weight, and the amount of the film-forming additive is in the range of 2.0 parts by weight to 12.0 parts by weight; preferably, the amount of the electrolyte additive is in the range of 0.3 parts by weight to 0.5 parts by weight, and the amount of the film-forming additive is in the range of 2.25 parts by weight to 11.50 parts by weight.

10. The electrolyte according to claim 8, characterized in that The film-forming additive is selected from fluoroethylene carbonate, vinylene carbonate, halogenated cyclic carbonate, sulfonate, acid anhydride, polynitrile compound, diisocyanate compound, phosphate, borate or any combination thereof.

11. The electrolyte according to claim 6, characterized in that The lithium salt is selected from LiCl, LiBr, LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2F)2, LiN(SO2CF3)2, LiC(SO2CF3)3, LiAlCl4, LiSiF6, or any group thereof.

12. The electrolyte according to claim 6, characterized in that The organic solvent is selected from ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate or any combination thereof.

13. A lithium ion secondary battery, characterized in that: include: Positive electrode, Negative electrode, Diaphragm, and The electrolyte according to any one of claims 6 to 12.